ISO/IEC 17020 accreditation of Gauteng Veterinary Services: a systems approach towards managing food safety in South Africa. (3rd January 2012) - Govender, Reuben; Katsande, Tendai Charles
Consumers worldwide demand safe food that is produced in facilities that meet high quality and safety standards. There has been an evolution in legislative control regarding the safe processing of meat in South Africa. Legislation has been amended in order to strengthen government control of safe meat production. Abattoirs are legally compelled to implement the hygiene management system (HMS), a documented and auditable basic food safety system that is audited using a tool known as the Hygiene Assessment System. Reliability and credibility of audit findings is critical in providing a high degree of assurance to the public regarding the production of safe meat. Gauteng Veterinary Services (GVS), South Africa, improved this reliability by implementing the ISO/IEC 17020 management system. This paper reviews the systems approach adopted by GVS to quality assure the processing of safe meat at abattoirs in the Gauteng Province of South Africa.